Implementation of Principal Academic and Managerial Supervision of Elementary School Teacher Discipline - Saidah; Syarifuddin Cn Sida; Muhajir (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to determine the implementation of supervision, principal managerial as well as the supporting and inhibiting factors of elementary school teacher discipline on the geometry material content. This type of research uses descriptive qualitative type. This research was conducted in schools. The subjects in this study were the Principal and Teachers. Data collection techniques using observation and interview techniques. The data analysis technique uses the Miles, Huberman, and Saldana model which consists of data collection, data condensation, data presentation, and drawing conclusions. Testing the validity of the data using triangulation of methods and theoretical. Based on the results of the research and discussion obtained, the conclusions in this study are: Implementation of Academic and Managerial Supervision of School Principals on Teacher Discipline. Principals and teachers carry out academic supervision when learning refers to aspects, namely: planning, implementation, and feedback. The planning process begins with the coordination of the supervision team, namely the principal, communication of objectives, and administrative preparation. Academic supervision is carried out through assessments by principals and teachers. Feedback is given in the form of discussions and awards for outstanding teachers. Aspects of assessment in the supervision and managerial of the principal include learning management, learning innovation, and attitudes and behavior. The process of implementing academic supervision during learning includes the planning, implementation and evaluation processes to foster teacher discipline towards school administration and responsibilities as teachers